The Issue of the Permanent Settlement of the Svaneti Territory, the Formation of the Svan Language From the Common Kartvelian Root Language, and the Resettlement of the Svan-speaking Kartvelian Population in the Bronze Age: Sokhumi State University - Argvliani, Irakli (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
Some of the cardinal issues of the ancient period of the history of the Svans and Svaneti is the issue of the permanent settlement of the Svaneti territory, the formation of the Svan language from the common Georgian root language, and the resettlement of the Svan-speaking Georgian population in the Bronze Age. Regarding these issues, a number of opinions have been expressed in the scientific literature, which, as a result of reconciling them with each other and re-interpreting archaeological and linguistic data, have led us to the following conclusions: The process of permanent settlement of the Svaneti territory should have begun by the end of the 3rd millennium BC, by the Georgian population, who were carriers of the Western Transcaucasia and Mtkvari-Araksi culture, of which the process of formation of the Svan-speaking Georgian population should have been carried out in the II millenium BC, on the territory lying north, northeast and northwest of the Rioni, including the southern slopes of the Caucasus. The area of ​​​​the eastern spread of the pre-Svans population should be conditionally referred to the Likhi ridge, and to the west, if not further, taking into account the information of Strabo (he places the settlement of the „Soanes“ above the Dioscurias at the turn of the century), at least to the Gumista River, of course, if the spread of the Svan-speaking population so far to the west is not a later event. The widespread settlement of the Svan-speaking population, both in the mountainous and plain regions of Western Georgia, should have taken place before the 30s-20s of the VIII century BC, before the destructive campaigns of the Cimmerians.